Conceptual design of reverse vending machine (RVM): Finite Element Analysis - Ismail, Al Emran; Hasan, Aiman (Research Progress in Mechanical and Manufacturing Engineering, 2022)
A reverse vending machine is a machine that uses the concept of giving rewards to those who recycle, but the price of this machine is expensive. The main objective for this research is to design a conceptual design of low-cost reverse vending machine and determined the stress, displacement and also analyse factor of safety for the component of reverse vending machine. This scope of study is this machine is only limited in receiving PET bottle, conducted in solidworks software and perform static analysis. Engineering design process which is conceptual design, embodiment design and detail drawing has been used to identify the suitable design. From the data, all the component that been chosen to conduct static analysis can be used in this machine. Not all the component in reverse vending machine is selected to perform analysis, therefore suggestion for future work is to perform analysis to other component as well with other analysis to build a real low-cost reverse vending machine.